Obesity and lipotoxicity - Engin, Ayse Basak; Engin, Atilla (Springer, 2017)
"Due to the resultant health consequences and considerable increase in prevalence, obesity has become a major worldwide health problem. "Obesity and Lipotoxicity" is a comprehensive review of the recent researches to provide a better understanding of the lipotoxicity-related mechanisms of obesity and the potential for the development of new treatment strategies. This book overviews the biochemical pathways leading to obesity-related metabolic disorders that occur subsequent to lipotoxicity. Chapters examine the deleterious effects of nutrient excess at molecular level including the cellular and molecular aspects of breast cancer, resistance to leptin, insulin, adiponectin, and interconnection between the circadian clock and metabolic pathways during high-fat feeding. "Lipotoxicity and Obesity" will be a useful resource for clinicians and basic science researchers, such as biochemists, toxicologists, immunologists, nutritionists, adult and pediatric endocrinologists, cardiologists, as well as students who are thought in this field"--Publisher's description.
Keywords: Obesity.; Lipids -- Metabolism -- Disorders.; elektronické knihy; electronic books